The Ascension of the Soul in Plotinus’ Enneads - Brandão, Bernardo (Revista de Filosofía, 2015)
according to Plotinus, it is possible for the soul of the philosopher to follow a way of ascension towards the superior realities. This way is composed of two parts. The first one goes from the sensible world to the Intellect and the second, from the Intellect to the one. In this paper, I investigate the trópos and mēkhanaí, as Plotinus writes in I, 6, necessary to this journey.